Algeria : The Real Exchange Rate, Export Diversification, and Trade Protection - Sorsa, Piritta (IMF Working Papers; Working Paper ;, 1999)
Given the tendency of the oil sector to appreciate the equilibrium real exchange rate (RER) in Algeria, trade liberalization with its depreciating impact on the RER is important for diversification of exports. This paper shows that reduction in trade protection would depreciate the RER in Algeria, which in turn would improve competitiveness of, and incentives to invest in, non-oil exports. The paper then discusses existing levels of protection in Algeria and directions for reform.